Towards a better understanding of the relationships between the structure and antitumor activity of Gastrodia elata polysaccharides by asymmetrical flow field-flow fractionation. (November 2021) - Dai, Shanshan; Zhang, Wenhui; Dou, Yuwei; Liu, Hongmei; Chen, Xue; Shi, Jianhong; Dou, Haiyang
Graphical abstract: Highlight: Effects of extraction time on the structure and conformation of PGEs were studied. Effects of the structure and conformation of PGEs on MCF-7 cells were investigated. PGEs with spherical and compact structure is benefit to its antitumor activity. AF4-MALS-dRI is a state-of-the-art technology for studying PGEs antitumor activity. Abstract: To better understand the structure–function relationship of Gastrodia elata polysaccharides (PGEs), PGEs were extracted by ultrasound-assisted extraction method and the effects of extraction time on the structure and conformation of PGEs were evaluated by asymmetrical flow field-flow fractionation (AF4) coupled online with multiangle light scattering (MALS) and differential refractive index (dRI) detectors (AF4-MALS-dRI). Besides separation, AF4-MALS-dRI can provide more information about PGEs, such as size and molecular weight ( M w ) distributions, apparent density, and conformation. The effects of PGEs on the proliferation, apoptosis, and cell cycle of MCF-7 cells were investigated. The cell activity assay indicated that the PGEs can inhibit the growth of MCF-7 cells by inducing late apoptosis. The results indicated that PGEs with a spherical conformation and compact structure seem to be beneficial to inducing MCF-7 cells late apoptosis. Moreover, results demonstrated that the information obtained by AF4-MALS-dRI is valuable for better understanding of the relationship of structure–activity of PGEs.